Two new species of the family Cunaxidae (Acari: Prostigmata) from Madagascar - Kalúz, Stanislav; Starý, Josef (Zootaxa, 2018)
Two new mite species from Madagascar, based on female specimens, viz. Armascirus skvarlai sp. nov. and Cunaxa corpuzrarosae sp. nov. (Acari: Prostigmata: Cunaxidae), are described and figured. Armascirus skvarlai sp. nov. differs from the related species A. gimpeli Smiley, 1992 by having long hysterosomal platelets, thin and long lateromedial sts on the palpal genu, and from A. ozarkensis Skvarla & Dowling, 2012 by having a cone-shaped proterosomal shield with straight lateral edges, and by its nearly triangular hysterosomal shield. Cunaxa corpuzrarosae sp. nov. differs from the related species C. potchensis Den Heyer, 1979 by having 4 pairs of sts between coxae IV and the genital region, and by having a short stout palpal femoral apophysis; and from C. mageei Smiley, 1992 and C. neogazella Smiley, 1992 by having much shorter hysterodorsal and palpal tibiotarsal setae.